ECONOMIC SUBSTANTIATION OF CREATION OF A MODERN RURAL TOURIST BASE OF REST - Madisheva Asem Maratovna; Sayabaev Kaisar Maksutovich; Zhetessova Mariyam Turashevna (Scientific Journal of Pedagogy and Economics, 2019)
Since the last century in most developed countries of the world green tourism has been used as one of the leading directions in the development of the tourist area, successfully implementing all the goals, objectives and principles of financial and economic activity of this area. In particular, the development of green tourism has intensified in the recent decades, spreading to not only developed states, but also on those that are in the stages of active and moderate development. Kazakhstan has not become an exception; one of the instruments for the development of this direction was “Green growth” initiative that by appropriate adaptation to the specific conditions of a country can be considered in the context of sustainable development.